2017
DOI: 10.5267/j.msl.2017.2.003
|View full text |Cite
|
Sign up to set email alerts
|

Employee satisfaction analysis with human resource index

Abstract: The objective of this research is to investigate employee satisfaction in one of Indonesian business firms named BM*. The study also tries to identify different factors influencing on employee satisfaction in the firm and to give appropriate suggestion for performance improvement. Methodology of this research is based on a survey and a questionnaire based on Human Resource Index (HRI) with measure 15 is used for the assessment. The results show that employee satisfaction of BM* was relatively high. However, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…More studies have been carried out during the last decade to investigate occupational stress. For example, studies found that level of occupational stress differ dramatically among employees due to some workplace factors such as workload, support, resources, control, recognition, person resiliency and compensation (Pagon et al, 2011;Prayogo et al, 2017). These studies argued that occupational stress is related to the negative impact on the well-being of employees in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…More studies have been carried out during the last decade to investigate occupational stress. For example, studies found that level of occupational stress differ dramatically among employees due to some workplace factors such as workload, support, resources, control, recognition, person resiliency and compensation (Pagon et al, 2011;Prayogo et al, 2017). These studies argued that occupational stress is related to the negative impact on the well-being of employees in the organization.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes associated with effective HRM practices are not limited to organisational performance as a singular concept. Links have also been found with flow (Kasa & Hassan, 2013), employee engagement (Albrecht et al, 2015), employee satisfaction (Prayogo, Pranoto, & Purba, 2017), organisational commitment (Chambel, Castanheira, & Sobral, 2016) and retention (Denkins, 2013), to mention only a few. Increasingly, researchers have focused on the vital association between HRM and corporate entrepreneurship (Dabic, Ortiz-De-Urbina-Criado, & Romero-Martínez 2011;Schmelter, Mauer, Börsch, & Brettel, 2010;Zhang & Jia, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%